Preprocedural Mouthrinse During Dental Treatment in Covid -19 Patients: A Meta- analysis - Sudan, Supinder; Ravishankar, T.L; Yavagal, Puja C.; Tafadar, M.D Nazamuddin (The journal of the Indian Association of Public Health Dentistry, 2024)
Abstract Background: The abrupt outbreak of the pandemic COVID-19 started in late 2019 caused widespread problems and issues. The capability to inactivate SARS-CoV-2 under biologically important conditions has not been evaluated till now systematically. As a result, the contribution of the use of mouthrinse before any dental treatment in reducing salivary viral load in COVID-19 patients is still unclear. Aim: The aim of the protocol is designed in PICO format as - patients taken are COVID-19 patients, intervention used is different mouthrinses, control taken as water, the studies included are clinical trials, and the outcome of the protocol is the efficacy of mouthrinses in reducing viral load. Review Methods: The registration of the protocol of the study was done under the number CRD42022325615 at the International Prospective Register of Systematic Reviews. The databases including Medline (through PubMed), Scopus, The Cochrane Controlled Clinical Trials Register, and Google Scholar were thoroughly searched from December 2019 to April 2022. The articles were analyzed using the RevMan 5.3 software. The inclusion criteria for selecting studies were based on cyclic threshold values and log copies/mL of salivary viral load. The quality assessment was performed based on the Cochrane risk of the bias assessment tool. Results: Eleven articles were included for systematic review, and out of these, eight articles were considered for meta-analysis. The result of the meta-analysis showed through forest plot which indicated that hydrogen peroxide 1% had potent antiviral efficacy at 30 min and 1 h of its use, whereas chlorhexidine and povidone-iodine effects were the same at 5 min and 1 h of their use. Conclusion: The preprocedural mouthrinse with hydrogen peroxide 1% reduces the salivary viral load in COVID-19 patients and prevents its transmission. This mouthrinse can be used 30 min before initiation of any dental treatment and even in between the procedure.